Effect of Acupuncture on Physical Symptoms and Quality of Life in Treatment-Resistant Major Depressive Disorder and Bipolar Disorder: a Single-Arm Longitudinal Study - Matsuura, Yuto; Hongo, Seiji; Taniguchi, Hiroshi; Yasuno, Fumiko; Sakai, Tomomi (Journal of Acupuncture and Meridian Studies, 2022)
Acupuncture is a non-pharmacological therapy used clinically for mood disorders. Relief of physical symptoms with acupuncture treatment may lead to relief of depressive symptoms and improvement of quality of life (QoL). Few studies have examined the effect of acupuncture on the physical symptoms and QoL of patients with mood disorders. To examine the effect of acupuncture on physical symptoms and QoL of patients with treatment-resistant major depressive disorder (MDD) and bipolar disorder (BD). This prospective, single-arm, longitudinal study included patients with MDD and BD from an outpatient psychiatric clinic. Acupuncture was performed weekly for 12 weeks in combination with regular treatment, with fixed acupoints and individualized treatment for each patient. Psychiatric symptoms were evaluated using the Himorogi Self-Rating Depression Scale (HSDS) and Himorogi Self-Rating Anxiety Scale (HSAS). Physical symptoms such as physical pain, gastrointestinal symptoms, and sleep disorders were evaluated using the Japanese version of the Somatic Symptom Scale-8 (SSS-8) and Visual Analog Scale (VAS). QoL was evaluated using the 8-item Short-Form (SF-8) Health Survey. A total of 36 patients (15 MDD and 21 BD patients) were analyzed. After 12 weeks of acupuncture, HSDS and HSAS scores significantly decreased ( < 0.05). Physical symptoms evaluated using SSS-8 and VAS scores also significantly improved ( < 0.05). In particular, neck pain and insomnia improved at an early stage. Among the SF-8 subscales, scores of bodily pain, general health perception, role limitations due to emotional problems, and mental health significantly increased ( < 0.05). Acupuncture may improve not only psychiatric symptoms but also physical symptoms and QoL in patients with treatment-resistant mood disorders. Further studies are required for confirmation of the preliminary data collected thus far.